Determinants of Economic Welfare of Persons with Disabilities in Bengkulu Province - Nopiah, Ririn (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
People with disabilities are classified as marginalized and vulnerable to poverty.  The condition of disability causes this group to experience accessibility barriers such as access to the fulfillment of the rights of persons with disabilities, especially in promoting disability welfare. Various factors are thought to be the cause of obstacles in achieving welfare. The purpose of this study is to analyze the factors that affect the economic welfare of persons with disabilities in Bengkulu Province. The analytical methods used are multiple linear regression and logistic regression. The results show that demographic factors such as domicile status, age, and number of household members affect the economic welfare of persons with disabilities. In addition, educational factors, Information and Technology skills, employment status, credit programs, government assistance (non-cash food assistance) also affect the economic welfare of persons with disabilities in Bengkulu Province. This is expected to be able to provide policy implications from local government agencies and other institutions in developing more effective and targeted programs.